(untitled) (Journal of the College of Basic Education, 2022)
We obtain generalization of best approximation for contractive condition of integral type and we next consider two results on invariant approximation also analyze the existence the application of fixed point and extend some known results of Habinik [7] ,Sahab [10], Kumar [5] Branciari [1], Singh [12].